Guardians of Oral Health: Antioxidants as Promising Allies in Periodontal Wellness - Arpita Mohapatra; Akshyata Panda; Naina Pattnaik; Madhumita Mohapatra; Karandeep Singh; Anant R. Sharma; Nirvi Sharma; Ramanpal S. Makkad (Wolters Kluwer Medknow Publications, 2024)
Periodontitis, a prevalent chronic inflammatory condition affecting the supporting structures of teeth, is closely associated with oxidative stress, characterized by an imbalance between reactive oxygen species generation and antioxidant defense mechanisms. Antioxidants have garnered significant attention as potential therapeutic agents in periodontal management due to their ability to counteract oxidative damage and inflammation. This brief review provides an overview of the role of antioxidants in periodontitis, highlighting recent developments. Key topics covered include the mechanisms of action of antioxidants, recent preclinical and clinical studies evaluating their efficacy, challenges, and future directions in antioxidant-based periodontal therapy. Recent advancements in antioxidant research offer promising avenues for improving periodontal treatment outcomes and patient care.